Hip Resurfacing. An Experience in Livingstone Hospital, Port Elizabeth, South Africa. From January 2004 to January 2006. - Pedro Gonzalo González González; Edgar Antezana Bilbao; Tamara Elizabeth Morales Perez (Medisur)
Background. Hip resurfacing in youngest patients with osteoarthritis is a very outstanding surgical technique which offer excellent results compare with a traditional Total Hip Replacement. Objective. To describe the evolution of the patients with osteoarthritis of the hip treated with the surgical technique of resurfacing in Livingstone Hospital. Port Elizabeth. South Africa. Method. A descriptive-retrospective study in the orthopedic department at Livingstone Hospital from January 2004 to January 2006. The variables used were the following: age, sex, affected hip, surgical approach and survivorship of the prosthesis at 12 moths-24 months after surgery. Results. Out of 30 patients operated 22 were males 73,3% the age group more affected was 46-55, 53,3%, the most common cause affecting the hip was the primary osteoarthritis in 17 patients 56,7% and the survivorship of the prosthesis 12 moths after surgery was 100%. Conclusions. Primary osteoarthritis of the hip is a health problem in male youngest patients and the surgical technique hip resurfacing is a very good choice.